John F. Kennedy collection - Kennedy, John F. (John Fitzgerald), 1917-1963.
Miscellaneous papers of or relating to Kennedy. Includes material concerning his presidential inauguration, his assassination and funeral, his will, and White House functions (1961-1963).
In part, photocopies.
U.S. president and U.S. senator from Massachusetts.
Keywords: White House (Washington, D.C.); Washington (D.C.) -- Social life and customs; Presidents -- United States; Senators, U.S. Congress -- Massachusetts